miR444b.2 –HsfA1– AOC1 module mediates heat priming–enhanced blast resistance in rice - Jiehua Qiu; Xiuxiu Cao; Huanbin Shi; Zhengting Chen; Xiaoyu Zhang; Zijian Cao; Dongmei Huang; Hui Wen; Ya Chen; Yanjun Kou (Proceedings of the National Academy of Sciences, 2025)
As global climate change exacerbates extreme heat events, the interplay between heat stress and blast disease resistance in rice remains poorly understood. In this study, through integrated transcriptome profiling and systematic phenotyping of mutants in several thermosensory pathways, we identified HsfA1 as a positive regulator of heat priming–enhanced blast resistance in rice. Systematic analysis of microRNA (miRNA) dynamics, bioinformatics prediction, and RNA pull-down experiments revealed that miR444b.2 , a temperature-responsive miRNA, directly suppresses the expression of HsfA1 by targeting the second exon of HsfA1 messenger RNA (mRNA). Genetic analyses demonstrated that heat stress–mediated suppression of miR444b.2 expression relieves the repression of HsfA1 , thereby enhancing blast resistance in rice. Furthermore, HsfA1 directly binds to the promoter of AOC1 , a key jasmonic acid (JA) biosynthesis gene, to activate its expression. Knockout of HsfA1 or AOC1 abolishes heat priming–enhanced JA accumulation and blast disease resistance, and the phenotypes are largely restored via AOC1 overexpression and MeJA treatment. Further identification of HsfA1 natural variants and generation of the HsfA1 uORF -edited lines with improved blast resistance offer potential strategies for breeding disease-resistant rice varieties. This study elucidates the miR444b.2 –HsfA1– AOC1 module that links thermal sensing to JA-mediated blast resistance, providing a molecular blueprint for engineering climate-resilient crops with concurrent biotic–abiotic stress tolerance.